Indicadores como base para gestão estratégica de supermercados varejistas - Costa, Wecsley Soares de Souza (2022)
This dissertation deals with store management as a competitive differential within retail organizations, especially supermarkets. Several bottlenecks, whether in management and/or operation within a store, can strongly impact your sales results, losses, stockouts, and, above all, the customer's shopping experience. This work aims to present a replicable model of management processes within a retail supermarket store. Thus, themes related to management, measurement of indicators, planning and routine of processes are taken as a reference, aimed at the development of strategies that mitigate problem situations, dealing with the set of methods and work standards of managerial activities and developing a model to be effectively implemented, with the standardization and documentation of processes in each sector. The study will take place through the development of two stages: the first, exploratory, which dealt with the revision of the theoretical framework and construction of the analysis model; and the second, of a conclusive nature, which was carried out by carrying out a survey of indicators such as sales and losses of the store and its categories. The methodology adopted is based on bibliographical studies, situation studies and solutions to field problems, with the collection of numerical data through the Consinco system (indicator management software), which, after being analyzed, can direct actions in order to generate points of improvement in the management, in addition to the case study with a deeper understanding of the processes defined as priorities. Finally, it is expected at the end of this research an improvement in the management of the store manager and the managers of each sector, bringing return to the company, in process improvements, customer satisfaction and financial results.